(untitled) (Journal of Educational Sciences, 2022)
The article considers the possibilities of a digital educational platform developed and partially prepared by a group of scientists within the framework of the scientific project of the KN of the Ministry of Education and Science of the Republic of Kazakhstan “Creating digital content for methodological support of Kazakh rural teachers of Russian language and literature in the organization of the educational process in a remote format”. Educational content is located at: https://auyl-school.kz/ The authors are currently working on the creation of digital educational resources to help teachers of the Russian language and literature of Kazakh schools, the content of which is completely tied to the Standard curriculum on the subject “Russian language and Literature”. The developed tasks can be applied by teachers in their lessons and the digital educational resources compiled for the primary school meet modern educational needs, contain video tutorials and audio materials, tests, presentations, simulators – collections of interactive tasks with automatic response verification, educational and methodological materials that a teacher can use to design online lessons and build effective interaction and organization of students’ work in a digital environment. The authors believe that the use of digital educational resources is justified, as it allows students to activate their activities, makes it possible to improve the quality of education, improve the professional level of a teacher, and diversify the forms of communication of all participants in the educational process. Key words: Russian language and literature, digital educational resource, educational content, interactive tasks.